Pelaporan Pajak Penghasilan Pasal 29 pada CV. ABC - Syainul Rahman (FAKULTAS ILMU SOSIAL DAN ILMU POLITIK, 2026)
Article 29 Income Tax is a tax that must be paid by taxpayers when the amount of income tax payable at the end of the fiscal year exceeds the available tax credits. Therefore, the reporting of Article 29 Income Tax must be carried out properly in accordance with the applicable tax regulations. This final project discusses the reporting process of Article 29 Income Tax at CV. ABC through Eka Prasetia Afandi and Partners Tax Consultant Office. The data collection methods used in this study were observation, interviews, literature review, and documentation. The data consisted of qualitative data in the form of observation and interview results, as well as quantitative data in the form of the company's commercial income statement and fiscal reconciliation report. The results show that the reporting of Article 29 Income Tax at CV. ABC was carried out through the preparation of a commercial income statement, fiscal reconciliation, corporate income tax calculation by utilizing the facility provided under Article 31E of the Income Tax Law, determination of Article 29 Income Tax, and reporting through the Coretax system as part of the submission of the Annual Corporate Income Tax Return. Based on the calculation results, CV. ABC had an underpayment of Article 29 Income Tax amounting to Rp59,423,086 and was therefore required to make the payment before submitting its Annual Corporate Income Tax Return. After the payment and reporting processes were successfully completed, the Coretax system issued an Electronic Receipt (BPE) as proof of tax return submission. Based on the discussion results, the reporting of Article 29 Income Tax at CV. ABC has been carried out in accordance with the applicable tax regulations.
Finalisasi Juli 2026 hasyim